2004
DOI: 10.1016/j.socnet.2004.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Academic communication and Internet Discussion Groups: transfer of information or creation of social contacts?

Abstract: This paper analyzes the role of Internet Discussion Groups (IDGs) in informal academic communication. It examines the claims in the literature that there are general benefits of academic mailing lists and newsgroups for researchers. Different hypotheses relating to potential contact and information benefits are tested with data of a random sample of English and Dutch university researchers within the humanities, the social and natural sciences. The outcomes support hypotheses about a few information effects an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 52 publications
2
56
0
2
Order By: Relevance
“…The use of bulletin boards, discussion groups and Usenet newsgroups has been reviewed in numerous studies since the 1980s both in work-related and non-work contexts (see, for example, Matzat, 2004;Savolainen, 2001). Some of the early studies reviewed information seeking in discussion groups.…”
Section: The Use Of Discussion Forums and Blogsmentioning
confidence: 99%
“…The use of bulletin boards, discussion groups and Usenet newsgroups has been reviewed in numerous studies since the 1980s both in work-related and non-work contexts (see, for example, Matzat, 2004;Savolainen, 2001). Some of the early studies reviewed information seeking in discussion groups.…”
Section: The Use Of Discussion Forums and Blogsmentioning
confidence: 99%
“…It is also remarkable that some studies on Facebook rely on server log data provided by the platform itself, which provides large samples, higher representativeness, objective information on what people really do on the platform, allowing for the distinction between social activities and individual pastimes like taking quizzes (see for example Burke et al 2010;2011). According to this strand of the literature, SNSs support the strengthening of bonding and bridging social capital (Steinfield et al 2008, Park et al 2009Pénard and Poussing 2010;Bauernschuster et al 2011), allow the crystallization of weak or latent ties that might otherwise remain ephemeral (Haythornthwaite 2005, Ellison et al 2007: 2011Miyata and Kobayashi 2008), facilitate the establishment of new collaborations in the academic community (Matzat 2004), support teenagers' selfesteem -encouraging them to relate to their peers (Ellison et al 2007;2011;Steinfield et al 2008), stimulate social learning (Burke et al 2010), enhance social trust (Matzat 2010), civic engagement (Stern and Adams 2010;Zhang et al 2010) and political participation (Gil de Zúñiga et al 2011), facilitate the creation of electronic networks of practice (Vasko and Faray 2005), and help the promotion of collective action (Landqvist and Teigland 2010). Drawing on survey data from a random sample of 800 undergraduate students, Ellison et al (2007) find that certain types of Facebook use can help individuals accumulate and maintain bridging social capital.…”
Section: Recent Studiesmentioning
confidence: 99%
“…According to Matzat (2004), many studies have shown that users of online discussions find that they are helpful for creating new ideas as well as providing research information. Garrison et al (2000) indicated that due to a greater time for reflection within text-based communications, they may be more preferable to oral communication when the objective is higher-order cognitive learning.…”
Section: Qualities Of Computer-mediated Conferencingmentioning
confidence: 99%
“…Previous research has looked at the length of messages and has concluded that while longer messages tend to be "richer" (in part resulting from more social presence cues), shorter messages generate more discussion postings (Schoberth et al, 2003). Similarly, in comparison to face-to-face communication, computer-mediated communication has found to be leaner and more task-oriented (Garrison et al, 2000;Matzat, 2004). This study investigates the ability of online textual communication, within an academic conference environment, to facilitate the depth of knowledge construction and critical debate.…”
Section: Qualities Of Computer-mediated Conferencingmentioning
confidence: 99%